2018
DOI: 10.3390/ijerph15112358
|View full text |Cite
|
Sign up to set email alerts
|

Window View and the Brain: Effects of Floor Level and Green Cover on the Alpha and Beta Rhythms in a Passive Exposure EEG Experiment

Abstract: With the growing interest among researchers, practitioners, and urban decision makers in the influence of the built environment on peoples’ health, there is increasing emphasis on using scientific knowledge to inform urban design, including methods of neuroscience. As window views are the most immediate medium of visual connection with one’s neighbourhood, we surmised that the quality of this view would have an impact on the mental health and well-being of urban dwellers. Accordingly, we investigated how windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 39 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…Studies of changes in brain waves in environmental and spatial stimuli have been conducted on a variety of topics, including studies of human emotions and relationships with architectural space [ 36 , 37 , 38 ], stress and anxiety [ 11 , 39 , 40 ], studies of positive and negative emotions [ 41 , 42 ], concentration and attention [ 43 , 44 ], and cognitive and emotional processing [ 9 , 14 , 45 ]. These studies have demonstrated that EEG is an appropriate tool for achieving research objectives.…”
Section: Application Of Vr-eeg In Architectural Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of changes in brain waves in environmental and spatial stimuli have been conducted on a variety of topics, including studies of human emotions and relationships with architectural space [ 36 , 37 , 38 ], stress and anxiety [ 11 , 39 , 40 ], studies of positive and negative emotions [ 41 , 42 ], concentration and attention [ 43 , 44 ], and cognitive and emotional processing [ 9 , 14 , 45 ]. These studies have demonstrated that EEG is an appropriate tool for achieving research objectives.…”
Section: Application Of Vr-eeg In Architectural Researchmentioning
confidence: 99%
“…Yasuhisa et al (2020) exposed each image stimulus for 6 seconds [ 67 ], whereas Wei-Yin et al (2019) presented 60 photos at random for 20 seconds [ 68 ]. Agnieszka et al (2018) presented 36 images at random for 10 seconds [ 41 ]. In this study, we interviewed the participants in the pilot experiment and found it took them 10 s to perceive a space without dozing off.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Second, this study was not able to include more individualized factors such as social and cultural differences, daylight preferences, preferred activity, etc. Third, not only is the indoor daylight intensity able to in uence the physiological condition of patients, but also the window view itself can generate positive physiological effects [28][29][30]. Our study cannot rule out the fact the possibility that the window view might play a more important role in affecting illiterate patients' recovery.…”
Section: Discussionmentioning
confidence: 86%
“…Patches in prefrontal areas were also involved in processing the number of street intersections. Using EEG, Olszewska-Guizzo et al (2015) [43] investigated how window views taken from different floors of a high-rise block with varying extents of green cover can impact the brainwaves of viewers. Their findings revealed the association between brainwave patterns and positive emotional states, motivation, and visual attention that may increase by the extent of green cover within window views from different floors of a high-rise block.…”
Section: Urban Environments Designmentioning
confidence: 99%